Explicit and Implicit Targets in Open Economies - Sgherri, Silvia (IMF Working Papers; Working Paper ;, 2005)
Under a flexible inflation targeting regime, should policymakers avoid any reaction to movements in the foreign exchange market? Using data for six advanced open economies explicitly targeting inflation, the paper examines empirically whether real exchange rate disequilibria systematically affect the conduct of monetary policy. Estimates indicate that monetary policy responses in inflation-targeting, open economies have changed significantly, as the institutional framework for the conduct of monetary policy has evolved. In particular, an explicit target for core inflation and a greater use of the expectation channel of monetary policy appear to be key features of the newest policy framework. In this context, central banks are unlikely to react to regular fluctuations in the exchange rate.